Meta-Analisis Pengembangan Media Pembelajaran Android Pada Materi Koloid - Putri, Larasati Ayu Putri; Fatah, Abdul Hadjranul; Asi, Nopriawan Berkat (FKIP Universitas Palangka Raya, 2024)
Meta-analysis is an activity that involves identifying, evaluating, and interpreting relevant research to systematically combine the results of existing studies. This research aims to analyze central tendency, variation, and errors in studies. This research uses four theses related to the development of Android-based learning media on colloid material. This research employs a quantitative meta-analysis method with the following steps: 1) Searching for sources and identifying thesis documents, 2) Expert assessment by media experts, material experts, and students, analyzing N and I values, 3) Calculating effect size and standard error, 4) Creating a forest plot for the effect size and standard error values. The results of the study are as follows: In the development studies of Android-based learning media on colloid material, media experts, material experts, and students have different percentage levels due to differences in location, research subjects, and media used. The assessment by media and material experts most suitable for Android-based colloid learning, reviewed from effect size and forest plot, is in study or research NA-22. In the material expert assessment, study RS-19 is the most suitable evaluation to obtain student responses for the development of Android-based learning media on colloid material.